DIGITAL GATEKEEPERS AND COMPETITION LAW: TOWARDS NEW RULES FOR PLATFORM DOMINANCE - Kayumov Asadulla Urolovich (Scholar Express Journals, 2025)
This article examines the growing influence of digital gatekeepers—large online platforms that control access to digital markets—and the challenges they pose to existing competition law frameworks. It explores how traditional antitrust principles struggle to address new forms of market power rooted in data concentration, network effects and algorithmic control. Drawing on recent policy developments such as the EU’s Digital Markets Act (DMA) and proposals in the United States, the paper highlights the emergence of ex-ante regulatory approaches aimed at preventing the abuse of platform dominance. The study also discusses implications for global competition policy and suggests directions for crafting more effective legal rules to maintain fair competition in digital ecosystems.
Keywords: digital gatekeepers; platform dominance; competition law